Effects of Endodontic Irrigants on Material and Surface Properties of Biocompatible Thermoplastics - Michael Kucher; Martin Dannemann; Niels Modler; Christian Hannig; Marie-Theres Weber (MDPI AG, 2019)
Passive irrigation is an efficient method for a successful endodontic treatment. During sonic activation biocompatible polymer tips are used to activate irrigants. Compared to ultrasonic activation with metallic tips, polymer tips have the advantage of a reduced risk of fracture and minimise dentine damage. Hence, two polymers, polyether ether ketones (PEEK) and polyamide (PA6), were identified for the manufacturing of novel irrigation tips. The chemical resistance against the irrigants ethylenediaminetetraacetic acid (EDTA) 20%, chlorhexidine gluconate (CHX) 2% and sodium hypochlorite (NaOCl) 5.25% was analysed. Using microindentation, the change of hardness, elasticity, surface roughness and appearance of the polymers was determined. PA6 had a high absorption of irrigant compared to PEEK. PEEK was resistant to the investigated irrigants and showed no significant alteration of surface and mechanical properties, whereas PA6 slightly increased its hardness, elastic modulus and surface roughness during long-term exposure at 37 °C. However, PA6 tips seem to be a promising disposable product due to the material’s high deformability and low manufacturing costs. Particularly with regard to structural-dynamic properties and high chemical resistance, PEEK can be considered as a material for reusable irrigation tips.